Innovativeness and creativity in Ho Chi Minh’s political thought - Ong Van Nam (Journal of State Management, 2024)
Ho Chi Minh's political thought is a system of perspectives formed and developed throughout his extensive political career. It is a distinctive political ideology that has profoundly influenced Vietnam’s history and politics. Ho Chi Minh absorbed the Marxist-Leninist theory, creatively and flexibly applying it to Vietnam’s specific context, emphasizing the integration of theory with practice and advocating the necessity of struggle for national independence and the people's freedom. This article analyzes and evaluates the central points of Ho Chi Minh's political thought, demonstrating its creative and innovative adaptation to Vietnam’s revolution.